THE UNIQUE STYLE OF THE MADIR POTTERY SCHOOL - Shahobitdinov son of Khayotbek Khakimjon; Buvayev Vohobjon Sadikovich (American Journals, 2023)
Applied decorative art - as a branch of decorative art, the preparation of artistic objects of practical importance in social and personal life and daily life items (tools, furniture, fabric, work tools, clothes, jewelry, etc.) (toys, etc.) includes creative fields of work related to artistic work.
Keywords: aesthetic imagination, anthropomorphic themes, Madir pottery school, majolica decoration, collective creativity, artistic traditions, set of patterns.